On the Spur of Speed : Continuing the Account of the Life and Times of Geoffrey Frost, Mariner, of Portsmouth, in New Hampshire, as Faithfully Translated from the Ming Tsun Chronicles, and incorporating an Account of Joseph Frost's and Juby's Conduct on Lake Champlain, all Dili - Fender, J. E. (Book collections on Project MUSE., 2005)
The shaping of a hero and a key battle of the American Revolution.